Observations of spatial and physical characteristics in the public space environment as a measurement parameter of visual comfort - Ghoustanjiwani Adi Putra; Daim Tri Wahyono (Green Visioneers, 2020)
This descriptive qualitative study is part of the prelimanary study which aims to examines of spatial and physical characteristics in the public space environment as a measurement parameter of visual comfort on the quality of the environment public open space. The author will conduct a qualitative descriptive analysis using literature data and results of previous studies in evaluating the quality of public spaces based on visual quality. This case study takes an object in the form of green open space,